Herta Müller : Politics and Aesthetics - Brandt, Bettina (Book collections on Project MUSE., 2013)
Two languages - German and Romanian - inform the novels, essays, and collage poetry of Nobel laureate Herta Müller. Describing her writing as "autofictional," Müller depicts the effects of violence, cruelty, and terror on her characters based on her own experiences in Communist Romania under the repressive Nicolae Ceauşescu regime. This book explores Müller's writings from different literary, cultural, and historical perspectives. The first part features Müller's Nobel lecture, five new collage poems, and an interview with Ernest Wichner, a German-Romanian author who has traveled with her, and sheds light on her writing. Parts two and three, featuring essays by scholars from across Europe and the United States, address the political and poetical aspects of Müller's texts. The contributors discuss life under the Romanian Communist dictatorship while also stressing key elements of Müller's poetics, which promises both self-conscious formal experimentation and political intervention. This volume addresses audiences with an interest in dissident, exile, migration, experimental, and transnational literature.